2013
DOI: 10.4037/ajcc2013838
|View full text |Cite
|
Sign up to set email alerts
|

Thematic Analysis of Cardiac Care Patients’ Explanations for Declining Contribution to a Genomic Research-Based Biobank

Abstract: Background Health care delivery systems increasingly ask patients to contribute biological samples for future genomic-based health research during critical care admissions, as the result of genome-based research requirements of unprecedented large sample sizes. Few reports describe patients’ perceptions and responses to actual biobanking approaches in clinical settings. A qualitative study was conducted to explore 568 cardiac care patients’ explanations of why they declined to contribute their samples to a fut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Of these, finally 10 articles were included in this study [ 36 45 ]. Reasons for exclusion at this stage were mainly due to lack of focus on participants’ perceptions or views regarding information or consent, for example [Hobbs et al [ 46 ], Ridgeway et al [ 47 ], Steinsbekk et al [ 48 ], Williams et al [ 49 ], or as the focus was on subjects who had not been involved in a consent procedure regarding biobank research, for example Rahm et al [ 50 ], or because the focus was on consent with parents of children donors, for example Tindana et al [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…Of these, finally 10 articles were included in this study [ 36 45 ]. Reasons for exclusion at this stage were mainly due to lack of focus on participants’ perceptions or views regarding information or consent, for example [Hobbs et al [ 46 ], Ridgeway et al [ 47 ], Steinsbekk et al [ 48 ], Williams et al [ 49 ], or as the focus was on subjects who had not been involved in a consent procedure regarding biobank research, for example Rahm et al [ 50 ], or because the focus was on consent with parents of children donors, for example Tindana et al [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…A qualitative study was done to investigate 568 cardiac care patients' reasons for declining such a contribution, and the researchers reported that themes of intrusion and autonomy dominated patients' explanations. 105 …”
Section: Ethicsmentioning
confidence: 99%
“…Using predetermined codes in addition to inductive reasoning is a practical approach for health services research that aims to develop taxonomy, themes, and theory (Bradley et al, 2007). The PI conducted an iterative process of line-by-line content analysis resulting in categorical data reduction that produced the reported themes (Elo & Kyngas, 2008;Graneheim & Lundman, 2004;Williams, Nemeth, Sanner, & Frazier, 2013). An expert qualitative researcher then verified the coded data to ensure rigor (Graneheim & Lundman, 2004).…”
Section: Data Collection and Analysismentioning
confidence: 99%